Electroreduction of p-Chlorobenzaldehyde by Galvanostatic Method - Madhu, Ms. (Asian Journal of Chemistry, 2010)
Electroreduction of p-chlorobenzaldehyde has been studied at metal electrode like nickel under acidic conditions using galvanostatic method. Polarization curves drawn in presence and absence of depolarizer indicated the proper range of current densities to be investigated. Isolated product was characterized to be p-chlorobenzyl alcohol by TLC, usual functional group tests, IR and NMR spectral analysis. Effect of various parameters such as current density, temperature, medium concentration, depolarizer ratio and nature of cathode material on yield percentage have been investigated.